Analysis of Efficiency for Space-Time Processing of Signals from Subscriber Stations in Implementation of Space-Time Division Multiple Access - Moskalets, M.; Teplitskaya, S. (KHARKIV NATIONAL UNIVERSITY OF RADIO ELECTRONICS, 2015)
It is shown that implementation of the method of space-time division multiple access with the individual space-time processing of subscriber stations signals which is reduced to the use of group elements of adaptive antenna array and the establishment of parallel procedures of assessing values of vector of weighting coefficients on the number of simultaneously working stations
Keywords: TELECOMMUNICATIONS; space-time division multiple access; space-time processing; beamforming; multi-beam antenna; vector of weighting coefficients